1991
DOI: 10.1007/bf00587641
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas transplantation: assessing secondary complications and life quality

Abstract: Two sequential studies of life quality among pancreas transplant recipients are reported. The first study (n = 32) investigated symptoms of neuropathy, enteropathy and retinopathy, along with well-being post successful transplantation. Patients noted improvement in secondary complications, were satisfied with the procedure and expressed hope for the future. The second study compared physical and social function, burden of symptoms, emotional/mental state and sense of well-being in successful (n = 31) and succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 3 publications
(2 reference statements)
0
7
0
1
Order By: Relevance
“…11-13 Several studies have reported stabilisation of retinopathy in up to 75% of successful SPK transplant recipients 910 13 14 In contrast, a number of prospective studies have reported that metabolic normalisation of glycaemia in successful SPK transplants has no effect on the subsequent course of diabetic retinopathy 815-19These studies have monitored the course of DR in successful SPK transplants recipients and compared them with less than ideal control groups which consisted of either failed SPK transplant recipients or kidney alone transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…11-13 Several studies have reported stabilisation of retinopathy in up to 75% of successful SPK transplant recipients 910 13 14 In contrast, a number of prospective studies have reported that metabolic normalisation of glycaemia in successful SPK transplants has no effect on the subsequent course of diabetic retinopathy 815-19These studies have monitored the course of DR in successful SPK transplants recipients and compared them with less than ideal control groups which consisted of either failed SPK transplant recipients or kidney alone transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, solitary pancreas transplantation is performed to make diabetic patients insulin injection-independent, and diabetes is not immediately life threatening. Successful pancreas transplant patients perceive their health as good and have a greater ability to function socially, with life quality becoming better over time (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the quality of life and the complications, deriving from diabetic status, have more benefits from pancreas transplantation than from insulin therapeutic plan or from islets encapsulation [29,30].…”
Section: Pancreas Transplantationmentioning
confidence: 99%